Computer-aided engineering and design of internal combustion engines to support operation on non-traditional fuels - Valles Castro, Miguel, author; Windom, Bret C., advisor; Marchese, Anthony J., committee member; Daily, Jeremy, committee member (Colorado State University. Libraries, 2020)
Traditional fuels like gasoline and diesel make up ~37 % of the US energy production; because of that, they are rapidly depleting their finite resources. These traditional fuels are also primary contributors to greenhouse gases, global warming, and particulate matter, which are bad for the environment and human beings. For that reason, research in non-traditional fuels (e.g., Carbon neutral biofuels, low GHG emitting gaseous fuels including NG and hydrogen) that achieve greater if not similar efficiencies compared to traditional fuels is gaining traction. On top of that, emission requirements are becoming even more strenuous. Engineers must find new ways to investigate non-traditional fuels and their performance in internal combustion engines while permitting the engine-fuel system's low-cost design. This being the case, Computer-Aided Engineering (CAE) tools like Computational Fluid Dynamics (CFD) and chemical kinetics solvers are being taken advantage of to assist in the research of these non-traditional fuel applications. This thesis describes the use of CONVERGE CFD to investigate two different non-traditional fuel applications, namely, the retrofitting of a premixed gasoline two-stroke spark-ignited (SI) engine to function with multiple injections of JP-8 fuel and to retrofit a diesel compression-ignited engine into a premixed anode tail-gas SI engine. The first application described herein uses a solid oxide fuel cell "Anode Tail-gas," which has similar syngas characteristics in a spark-ignited engine. Anode Tail-gas is a byproduct from an underutilized Metal Supported Solid Oxide Fuel Cell (MS-SOFC) used in a high efficiency distributed power (~100 kWe) system. Gas turbines or reciprocating ICEs typically drive distributed power systems of this capacity because they can quickly react to change in demand but traditionally have lower thermal efficiencies than a large-scale Rankine cycle plant. However, with the MS-SOFC, it may be possible to design a 125 kWe system with 70 % efficiency while keeping the system cost-competitive (below $1000/kW). The system requires a ~14 kW engine that can operate at 35 % efficiency with the highly dilute (17.7% H2, 4.90 % CO, 0.40% CH4, 28.3 % CO2, 48.7 % H2O) Anode Tail-gas to meet these lofty targets. CAE approaches were developed and used to identify high-efficiency operation pathways with the highly diluted anode tail-gas fuel. The fuel was first tested and modeled in a Cooperative Fuel Research (CFR) engine to investigate the anode tail gas's combustibility within an IC engine and to provide validation data with highly specified boundary conditions (Compression Ratio (CR), fuel compositions, intake temperature/pressure, and spark timing). A chemical mechanism was selected through CAE tools to represent the highly diluted fuel combustion best based on the CFR data. Five experimental test points were used to validate the CFD model, which all were within a maximum relative error of less than 8 % for IMEP and less than 4 crank angle degrees for CA10 and CA50. The knowledge gained from the CFR engine experiments and associated model validation helped direct the design of a retrofitted Kohler diesel engine to operate as a spark-ignited engine on the anode tail gas fuel. CFD Investigations into spark plug and piston bowl designs were performed to identify combustion chamber design improvements to boost the Kohler engine's efficiency. Studies revealed that piston designs incorporating small clearance heights, large squish areas, and deep bowl depths could enhance efficiency by 5.41 pts with additional efficiency gain possible through piston rotation. The second fuel investigation was a jet propellant fuel called "JP-8," which was deemed non-tradition when used in a two-stroke UAV engine to satisfy the military's single fuel policy requirements. The JP-8 fuel proved challenging in this application due to its significantly lower octane number and volatility than gasoline and experienced knock when used as a homogeneous premixed mixture within the simulated UAV platform. Although with CFD modeling, it was possible to reduce the severity of knock by using eight rapid direct injections of JP-8 at 20 µm diameter droplets. With further investigation, it might be possible to reduce further the severity of knock using CFD through more advanced injection strategies.
Keywords: dilute fuel; internal combustion engines; solid oxide fuel cell; engineering design; computer aid engineering; single fuel policy